PERAN KEPALA SEKOLAH DALAM MEMBERDAYAKAN TENAGA PENDIDIK - Mukhammad Bakhruddin (EL-Islam, 2021)
This article is the result of field research related to the principal's role in empowering educators. The research was backed by anxiety, the idea that, the principal's role is reduced to the role of administrators, managers, and supervisors of the programs launched in educational institutions. In fact, should be, the role of the principal is more comprehensive terminology theoretically framed. The important thing is, a school principal should be able to cultivate the effectiveness of the planned program, innovative in taking decisions, as well as efficient in terms of time management. All this must be internalized within the principal. In order, any programs that have been proposed could be implemented carefully. This research, qualitative research shaped by the content analysis model. In conclusion, the results of this study revealed that, discipline, collective colegial, and build a culture that is professional, the key to success leadership in SMA Muhammadiyah 2 Surabaya. Without the need to separate when the principal role as administrator, leader, manager, and supervisor.